Use of Two Online Services as Drug Information Sources for Health Professionals - Abatea, M. A.; Shumwayb, J. M.; Jacknowitzc, A. I. (Methods of Information in Medicine, 1992)
The utility of the online computer services BRS Colleague and Dialog Medical Connection, when used primarily as drug information sources by physicians, nurses, and pharmacists and attitudes toward their use, are described. Study sites included office-based medical practices, a university clinic family medicine group, and a university clinical pharmacy department. Participants had access to either of the computer services during two 9½-month periods. All searches were automatically recorded and analyzed. A total of 1,112 search sessions were conducted (78% by pharmacists, 16% by nurses, 6% by physicians) by 38 of 65 participants. Information which completely answered questions was found for slightly less than one-third of searches. Errors occurred in about 81% of searches which retrieved incomplete information. Lack of time was a major factor which limited use of the services, and infrequent users felt that the services did not fit in well with their daily work routine.
Keywords: Online Systems; Physicians; Pharmacists; Nurses; Information Services